Exploring stress and morphology in two songbird species across urban, agricultural, and natural habitats on San Cristobal Island, Galapagos - Andrés Mena; Martín Terán; Diana Calderón; Maria de Lourdes Torres; Diego F. Cisneros-Heredia (BMC Zoology)
Abstract Land use changes can have morphological and physiological impacts on wildlife. This study aimed to explore the influence of anthropogenic land use on the morphology and corticosterone concentrations in two songbirds endemic to the Galapagos archipelago: the granivorous Small Ground Finch Geospiza fuliginosa and the insectivorous Galapagos Yellow Warbler Setophaga petechia aureola in San Cristobal Island. Birds were caught and measured between June and August 2018 and June and July 2019 across four areas with different human land uses: urban green areas in the coastal town of Puerto Baquerizo Moreno, natural deciduous forest in the lowlands, agricultural areas in the highlands, and seasonal evergreen forest in the highlands. Morphological comparisons among study areas were made using ANOVA or the Kurskall-Wallis test. Corticosterone levels obtained from tail feathers were measured with an ELISA test. Linear regression models were employed to explore the effects of the different human land uses on corticosterone concentrations. For G. fuliginosa, we found significant differences (p < 0.05) in weight, wing, and tarsus length between natural and disturbed habitats. The linear regression results showed higher corticosterone concentrations in urban G. fuliginosa than those in agricultural and natural habitats. Additionally, higher corticosterone concentrations were found in finches captured in 2018, a year with much higher precipitation than in 2019. For S. petechia aureola, the only significant difference (p < 0.05) between areas was a wider beak in birds captured in the seasonal forest compared to those from urban areas. Although our sample size does not allow for definitive conclusions, our results provide evidence that the ecology of each species plays a crucial role in shaping their morphological and physiological responses to land use changes and seasonal environmental changes.